Boomerang Employee Sebagai Model Alternatif Rekrutmen SDM: Studi Kasus Di PT. Delta Djakarta, Tbk - Prakoso, Yusak (CV. Ulil Albab Corp, 2024)
This research was done to examine the implementation of boomerang employees. The phenomenon of boomerang employees has become a prevalent and accepted practice in many organizations, as it is perceived as a strategic advantage. To date, the concept has advantages and disadvantages based on numerous studies conducted to illustrate the implementation of the boomerang employee process. This research employs qualitative descriptive methodology, involving seven key informants: one individual from the field of Human Resource Management, three individuals from the organization who have direct interactions with boomerang employees, and three boomerang employees themselves. The findings of this research indicate that PT. Delta Djakarta employs a boomerang employee procedure as a component of its human resource strategy to address its personnel requirements. The objective of utilizing the boomerang employee framework from the organizational perspective and that of the boomerang employee at PT. Delta Djakarta. This research discusses the requirements that must be fulfilled for boomerang employees, the impact of boomerang employees, and the obstacles experienced by both organizations and the boomerang employees themselves.